Understanding the facilitators and barriers to barcode medication administration by nursing staff using behavioural science frameworks. A mixed methods study - Kate Grailey; Rabia Hussain; Elisa Wylleman; Ahmed Ezzat; Sarah Huf; Bryony Dean Franklin (BMC, 2023)
Abstract Introduction Barcode medication administration (BCMA) technology helps ensure correct medications are administered by nursing staff through scanning of patient and medication barcodes. In many hospitals scanning rates are low, limiting the potential safety benefits. We aimed to explore the barriers and facilitators to BCMA use in a London hospital. Methods In this mixed methods study we used local quantitative data on BCMA scanning rates to identify clinically similar wards (in terms of patient acuity and workload) with different scanning rates for qualitative exploration. Interviews designed to elicit barriers to using BCMA technology were conducted with nursing staff, supported by observations of medication administration. Qualitative data were analysed inductively and a thematic framework constructed housing key themes, subsequently categorised into barriers and facilitators. To explore patient perspectives of BCMA scanning, a purposive sample of patients were also interviewed. These patient data were analysed deductively according to the thematic framework. Themes were mapped to behavioural science frameworks to further understand the behaviours involved. Results BCMA was operational on 15 wards, with only six having medication scan rates of more than 10% of scannable doses. Of three wards selected for qualitative investigation, the lowest scan rate was 6.7%. Twenty-seven nurses and 15 patients were interviewed. Eleven key themes were identified, encompassing both barriers and facilitators to BCMA use. Barriers included poor trolley ergonomics and perceived time inefficiency. Facilitators included a streamlined process and thorough training. All nurses described BCMA as positive for patient safety. Patients described BCMA as making them "feel safer". Behavioural science frameworks highlighted the importance of professional role and an individual's belief in their capability. Conclusion We present a novel exploration of facilitators and barriers to BCMA use from the viewpoint of both patients and nursing staff, highlighting a strong perception that BCMA enhances safety. Barriers were reported on both high and low usage wards, demonstrating the importance of behaviours and motivations. These findings provide a detailed understanding from which to design interventions to support behaviour change and increase BCMA use.